How robust is the recent strengthening of the Tropical Pacific trade winds?. Issue 12 (26th June 2014) - de Boisséson, E.; Balmaseda, M. A.; Abdalla, S.; Källén, E.; Janssen, P. A. E. M.
Abstract The persistent strengthening of the trade winds over the Pacific Ocean over the past 20 years has recently been proposed as a driver for the increase of ocean heat uptake linked to the hiatus in surface global warming. Crucial aspects in this argument are the reliability of the wind signal, usually derived from atmospheric reanalyses, and the ability of models to represent it. This study addresses these two aspects by comparing various observations with reanalyses and model integrations from the European Centre for Medium‐Range Weather Forecasts system. We show that the strengthening of trades over the Pacific is a robust feature in several observational data sets as well as in the reanalyses based on full and limited sets of observations. The wind trend is also reproduced in an atmospheric model integration forced by sea surface temperature analysis, a result that opens the doors to further investigation on the nature of the changes.